Taxonomic study of two Trichogramma species from Uruguay (Hym.: Trichogrammatidae) - Baáo, C.=700 1 Pintureau, B.; Grille, G.
Resumenes (Es, En)
4 c; 26 ref.
Keywords: TRICHOGRAMMA; PARASITOIDES; CONTROL BIOLOGICO; TAXONOMIA; CRUZAMIENTO; ESTERASAS